HAPPY HEALTH SNACK PROGRAM: AN EFFORT TO ADDRESS FOOD INSECURITY IN SCHOOLS IN SOUTHEAST KANSAS - Bell, Janae (My University, 2025)
This integrated learning report provides a comprehensive review of my educational experience in completing the Applied Practice Experience (APE). I completed this project with K-State Research and Extension (KSRE) Wildcat Extension District, assisting in the expansion of the Health Happy Snack Project (HHSP). The HHSP is a nutrition curriculum implemented in southeast Kansas to address food insecurity in public schools. For this APE, I designed a nutrition-based curriculum for school-aged children in kindergarten through second grade. The goal of this project was to promote nutrition and wellness among early elementary students and to increase their knowledge of childhood nutrition and the MyPlate guidelines. The curriculum included nutrition lessons covering MyPlate categories, as well as hydration, handwashing, and food allergies. The lessons also included physical activity, tasting opportunities, in-class activities, and send-home recipes to promote family involvement after the in-school lessons. Additionally, I presented this curriculum to Blue Valley school nurses as part of professional development, offering one hour of credit for continuing education units (CEUs). I was also able to pilot the first lesson of the curriculum, hand washing, in local first and second-grade classrooms. I received feedback from nurses after the CEU presentation, and teachers following the handwashing lesson. This project allowed me to synthesize skills in program planning, health communication, and evaluation acquired throughout the MPH program.
Keywords: nutrition; nutrition education; Happy Healthy Snack Project; MyPlate; health promotion; childhood nutrition